Locoregional chemotherapy in primary and secondary neoplasms of the liver - review of the literature - Wcisło, Gabriel; Korniluk, Jan; Barzał, Justyna; Brzozowski, Krzysztof; Nurzyński, Paweł; Twarkowski, Paweł; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
Liver is the predominant site of metastatic disease from the large bowel. Ten percent to 25% of the patients undergoing operation for removal of a primary tumor of the colon and rectum are found to have synchronously occurring hepatic metastases. 2 years of following resection of the primary carcinoma, next 25% will have hepatic metastases. Five year survival rates were 20- 60% respectively of patients without resectional therapy for metastatic liver colorectal cancer and only >5% in patients after palliative therapy. Hepatic Arterial Infusion (HAI) is a palliative treatment for liver metastases in patients with colon cancer. The best concentrations of anticancer drugs in a tumor mass is to be if drugs are supplied by pathological vessels, mainly arteries in case of liver metastases. The idea has come true by isolated perfusion of liver with drugs taking advantage of microcatheter localized in hepatic arteries. Regional antineoplastic drug administration is not a new concept, having been examined since the earliest days of the modern chemotherapeutic era. For example, nitrogen mustard and hemisulfur mustard were administered by the intraperitoneal route in the 1950s as a strategy to treat malignant effusions. During the same time period alkylating agents were delivered via intraarterial instillation to treat localized tumor masses. The principal aim of all attempts to administer antineoplastic agents regionally was to increase the exposure of cancer cells to the drugs beyond what can be achieved sefely through systemic drug delivery. Opportunities to optimize efficacy through regional administration of antineoplastic agents: 1) increase exposure time of tumor to minimally or moderately active cytotoxic agents, 2) prolong exposure of tumor to cycle-specyfic cytotoxic agents, 3) decrease systemic toxicity associated with iv drug delivery, 4) enhance opportunity for concentration-dependent synergy between two or more antineoplastic drugs. Chemiotherapeutic agents used for HAI: 5-Fluoro-2-deoxyuridine (FUDR), 5-Fluorouracil, Mitomycin C, Cisplatin, Adriamycin (doxorubicin hydrochloride). HAI due to liver metastases in patients with colon cancer seems to be a palliative procedure. This appeared to be responsible for alleviation of hepatic disturbances. HAI due to liver metastases in patients with colon cancer seems to be a palliative procedure giving the possibility for longer live.